The management of microbial keratitis within Uganda’s primary health system: a situational analysis [version 1; peer review: 3 approved] - Arunga, Simon; Kyomugasho, Naome; Kwaga, Teddy; Onyango, John; Leck, Astrid; Macleod, David; Hu, Victor; Burton, Matthew (Wellcome Open Research, 2019)
Microbial keratitis (MK) frequently leads to sight-loss, especially when the infection is severe and/or appropriate treatment is delayed. The primary health system as an entry point plays a central role in facilitating and directing patient access to appropriate care. The purpose of this study was to describe the capacity of primary health centres in Uganda in managing MK. Methods: We carried out a rigorous assessment of primary health centres and mid-cadre training schools in South Western Uganda. Through interviews, checklists and a picture quiz, we assessed capacity and knowledge of MK management. In addition, we interviewed the heads of all the mid-cadre training schools to determine the level of eye health training provided in their curricula. Results: In total, 163 health facilities and 16 training schools were enrolled. Of the health facilities, only 6% had an Ophthalmic Clinical Officer. Only 12% of the health workers could make a diagnosis of MK based on the clinical signs in the picture quiz. Although 35% of the facilities had a microscope, none reported doing corneal scraping. None of the facilities had a stock of the recommended first line treatment options for MK (ciprofloxacin and natamycin eye drops). Among the training schools, 15/16 had an eye health component in the curriculum. However, the majority (56%) of tutors had no formal expertise in eye health. In 14/16 schools, students spent an average of two weeks in an eye unit. Conclusions: Knowledge among health workers and capacity of health facilities in diagnosis and management of MK was low. Training for eye health within mid-cadre training schools was inadequate. More is needed to close these gaps in training and capacity.
Keywords: Microbial Keratitis; Bacterial Keratitis; Fungal Keratitis; Blindness; Uganda Health System